IDENTIFICATION OF STUDENT GRADES USING THE SAW METHOD IN A DECISION SUPPORT SYSTEM - Rizka, Ade; Sari, Rahayu Mayang; Ulandari, Lavenia; Pratiwi, Daratika (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
The decision support system is one way to assist in making decisions based on calculation methods. Decisions often become a confusing obstacle because they have several considerations to make a decision. Several methods can be used to support a decision. The SAW method is a method that has results that can support decisions based on the weights and criteria of each alternative. Student ranking is always an achievement of the learning outcomes that have been carried out, so it requires appropriate validation or calculations and can be used as a ranking decision. In this case, identification was carried out using the SAW method to determine student rankings based on the academic scores obtained. Analysis and observation of constraints and ranking processes to support the calculation process. The results of this research indicate that the SAW method can be used in determining student rankings and can be applied to student assessment and ranking applications.